The parterre on the Svobody Avenue – a “visiting card” of modern Lviv - Petryshyn, Halyna; Lukashchuk, Halyna; Tupis, Stepan (Видавництво Львівської політехніки, 2016)
At the turn of the 19th – 20th centuries Lviv underwent an active urban development, becoming a significant European cultural center. This period was marked by the construction of a number of interesting large-scale, highly artistic architectural and urban ensembles which until now play an important role in the architectural self-identification of the city and its inhabitants. A special place in Lviv is occupied by Prospect Svobody (Svobody Avenue or Liberty Avenue), which, unfortunately, does not have the status of a protected site. Львів на зламі ХІХ–ХХ століть зазнав активного містобудівного розвитку, перетворюючись у значний європейський культурний осередок. Цей період відзначений зведенням низки цікавих, масштабних високомистецьких архітектурно-містобудівних ансамблів, які до сьогодні відіграють важливу роль у побудові самоідентифікації міста та його мешканців. Особливе місце Львові займає проспект Свободи, який на жаль не посідає пам’ятко-охоронного статусу.
Партерні сади на проспекті Свободи – “візитна картка” сучасного Львова
Keywords: Lviv; architecture and urban planning of early 20th century; Boulevard; landscape architecture; greenery; flower stalls; Львів; архітектура та містобудування початку ХХ століття; бульвар; садово-паркове мистецтво; зелені насадження